2007
DOI: 10.5714/cl.2007.8.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-Heat-Treatment on Various Characteristics of Commercial Pitch-Based Carbon Fibers

Abstract: In this study, commercially available pitch-based carbon fibers of general grade were post-heat-treated using a boxtype high temperature furnace at 1800°C, 2000°C, 2200°C, and 2400°C, respectively. The fundamental characteristics of each heat-treated carbon fibers were investigated in terms of chemical composition, morphology, thermal stability, X-ray diffraction, single filament tensile test, and electrical resistivity. The result showed that the fiber properties were significantly influenced by the post-heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In addition, the fiber morphology is developed with a preferred orientation [20]. Yoon et al [21] reported earlier that commercial pitch-based carbon fibers were post-heat-treated at high temperatures, significantly increasing some fundamental characteristics through post-heat-treatment.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fiber morphology is developed with a preferred orientation [20]. Yoon et al [21] reported earlier that commercial pitch-based carbon fibers were post-heat-treated at high temperatures, significantly increasing some fundamental characteristics through post-heat-treatment.…”
Section: Characterizationmentioning
confidence: 99%
“…The value increases as the carbonization temperature increases. It was reported that pitch-based carbon fibers with graphitic structures normally exhibit the resistivity of about a few hundred µΩ·cm [1,21]. …”
Section: Single Filament Tensile Propertiesmentioning
confidence: 99%